Use logistic regression to classify gifted school students - Mohamed, Tasneem kamaleldin (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to use Logistic Regression to categorize the binary variables which don’t follow the natural distribution national corporation data were used at the gifted and distinguished schools affiliated to the Ministry of Education in Sudan, The study used the descriptive, deductive and analytic methods, that through analyzing the study data, besides using the Statistic Package for Social Sciences (SPSS version 20) to treat data. The study concluded to where the authentic categorize rate of the logistic declension about (92%), and that the most important that effects the acceptance is the Wechsler test for measuring the intelligence talented, outstanding has no significant impact on the model, out of eleven variables and the rest of the variables have no significant on the model.